Highly conductive polymer/metal/carbon nanotube composite fiber prepared by the melt-spinning process. Issue 5 (March 2017) - Lim, Tae Hwan; Lee, So Hee; Yeo, Sang Young
Highly electrical conductive fibers have received significant attention because of their potential to be utilized for wearable technology. Conductive fibers have already been developed by many research groups using metal and carbon nanotubes (CNT); however, productivity is limited. Conductive fibers composed of conductive additives embedded in a polymer matrix were fabricated by a melt-spinning process. This enables the scaling-up of production and gives high mechanical strength compared to fibers prepared by other processes. Silver (Ag) was selected for the conductive material, and embedded in polypropylene (PP) fiber. However, the melt-spinning process has an inherently lower filler content threshold; therefore, it was difficult to fabricate with sufficient silver for the required electrical properties. CNT forests were introduced to make up for this shortcoming, and they could serve as a conductive bridge between unconnected Ag. The CNT percolation effect confirmed that non-conductive Ag/PP increases electrical conductivity after CNTs were added. It was determined that 80 nm Ag (46 wt%) and single wall CNT (4 wt%) embedded PP composite fiber (Ag80/SW_46/4) was the optimum fiber; with a thickness of less than 100 µm its electrical conductivity was 4.1–7.2 × 10 −2 S/cm. Conductive fabric was fabricated using our composite fiber, and it had higher electrical conductivity than that of a single fiber because multi-filaments induced lower electrical resistance. Although the electrical value attained does not approach a satisfactory goal, it is thought that this fiber has a potential to be applicable for wearable technology.